Constraints on deformation processes in Iceland from space geodesy: seasonal load variations, plate spreading, volcanoes and geothermal fields - Drouin, Vincent, 1989- (2016)
Iceland is subject to many ground deformation processes. High levels of volcanic and tectonic activity are caused by a hotspot underlain by excessive mantle upwelling interacting with a divergent plate boundary on the Mid-Atlantic Ridge. Glacial isostatic adjustments (GIA) induced by the melting of the ice caps generates uplift of a few centimeter per year in the central part of Iceland, and seasonal load variations generate signal of a similar amplitude on a yearly basis. This thesis focuses on the use of two techniques of space geodesy, Global Positioning System (GPS) measurements and interferometric analysis of synthetic aperture radar images acquired by satellites (InSAR), to improve understanding of the Earth movements. GPS measurements and InSAR analysis are used to provide constrains on ground deformation processes taking place in Iceland, in particular in the Northern Volcanic Zone (NVZ). The seasonal ground deformation observed at 72 continuous GPS stations in Iceland is compared to the seasonal cycle of various loads. The peak-to-peak amplitude of annual variations in vertical change ranges from 4-5 mm at the coast up to 27 mm in the center of Vatnajökull glacier. The observed spatial and temporal pattern of these annual fluctuations is reproduced by a model. The seasonal cycle of glaciers, snow on non-glaciated areas, atmosphere, ocean and water reservoirs loads can be inferred through inversion of the seasonal vertical component of the deformation using a multi-layered elastic spherical Earth model. There is a low rigidity anomaly beneath Iceland, likely caused by its particular tectonic setting. Another part of the study considers the Northern Volcanic Zone of Iceland. Repeated campaign GPS measurements between 2008 and 2014, a period free of magmatic intrusions, have been analyzed and interpreted. The zone accommodates the full plate spreading rate in Iceland of about 18 mm/yr and is ideal for the study of the plate spreading processes. Observations at 132 GPS sites reveal about 50-km wide ...